2021
DOI: 10.1111/all.14817
|View full text |Cite
|
Sign up to set email alerts
|

IgE‐cross‐blocking antibodies to Fagales following sublingual immunotherapy with recombinant Bet v 1

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…Here, allergic tolerance was correlated to both IgG 4 and IgG 1−3 . While the latter was not found to be statistically significant, it is consistent with other studies in which the protective effect of immunotherapy treatments is mediated by a plurality of IgG isoforms suggesting both the classic Th1 and modified Th2 response can contribute to tolerance ( 55 58 ). Despite its protective effects, the modified Th2/IgG 4 response is dependent on initial B-cell activation by IL-4.…”
Section: Anomalous Dose-response Curves Provide Insight Into the Mech...supporting
confidence: 90%
“…Here, allergic tolerance was correlated to both IgG 4 and IgG 1−3 . While the latter was not found to be statistically significant, it is consistent with other studies in which the protective effect of immunotherapy treatments is mediated by a plurality of IgG isoforms suggesting both the classic Th1 and modified Th2 response can contribute to tolerance ( 55 58 ). Despite its protective effects, the modified Th2/IgG 4 response is dependent on initial B-cell activation by IL-4.…”
Section: Anomalous Dose-response Curves Provide Insight Into the Mech...supporting
confidence: 90%
“…Instead, the patients who had received rBet v 1 induced a protective response to apple [ 174 ]. This latter finding has been shown in other allergens from fagal families [ 175 ].…”
Section: Benefits and Limitations Of Novel Immunotherapiessupporting
confidence: 82%
“…Although immunological methods have long been considered the gold standard for allergen identification, MS offers considerable benefits by allowing allergen identification based on MS/MS data from the allergen of interest [ 192 ]. For example, we have previously identified novel allergens from Ligustrum lucidum including enolase, pollen-specific polygalacturonases, Fra e 9.01 (β-1,3-glucanase), profilin, alanine aminotransferase, and ATP synthase beta subunit [ 175 ]. Using a similar approach, allergens from both red oak and pecan [ 189 , 191 ] have been recognized.…”
Section: Allergy Proteomicsmentioning
confidence: 99%
“…Recent data showed that ligand-binding played an important role in sensitization and manifestation of allergenic properties of Bet v 1 homologs and LTPs ( Fujimoto et al, 1998 ; Chruszcz et al, 2021 ). IgE antibodies to Bet v 1 cross-react with homologues allergens from pollen of such trees as alder (Aln g 1), hazel (Cor a 1), beech (Fag s 1), chestnut (Cas s 1) and others ( Grilo et al, 2021 ) as well as with Bet v 1-like proteins from nuts, fruits and vegetables, particularly, with the peanut Ara h 8 apple Mal d 1 ( Vanekkrebitz et al, 1995 ; Bohle et al, 2003 ), carrot Dau c 1 ( Zulehner et al, 2017 ), causing oral allergy syndrome (OAS) ( Costa et al, 2022 ) in 70% of birch allergic patients ( Högerle et al, 2022 ). Symptoms of OAS usually appear immediately after plant food consumption and mainly affect oropharyngeal area, but such severe reactions as anaphylaxis also may take place ( Högerle et al, 2022 ).…”
Section: Characterization Of Pollen Allergensmentioning
confidence: 99%
“…The cross-blocking bioactivity of these antibodies was highly variable and could not be predicted from protein homology or IgE cross-reactivity. Thus, immunotherapy with the reference allergen Bet v1 induces an individual repertoire of cross-reactive antibodies IgG1 and IgG4 ( Grilo et al, 2021 ).…”
Section: Sensitization To Pollen Allergensmentioning
confidence: 99%